The implementation of Islamic trade financing product by Islamic banking institutions towards Muslim Halal entrepreneurs (MHE) in Malaysia - Awang, Mohd Daud; Abdullah, Norsazali; Yahya, Hisham; Abdullah, Amini Amir; Ismail, Kamarulzaman; Jusoh, Mohd Kamal Azman (Human Resource Management Academic Research Society, 2023)
This paper is prepared to observe the implementation of Islamic trade financing products for Muslim Halal entrepreneurs (MHEs) who have obtained trade financing from Islamic banking institutions in Malaysia. Islamic banking institutions play an important role in developing Muslim Halal businesses and entrepreneurship and Halal entrepreneur economies. This study used qualitative research and in-depth views based on objectives. Interviews were conducted on respondents from bank officers of Islamic banking institutions and analysed the themes as identified by the researchers. The findings of this study show that Islamic banking institutions have successfully their extensive role in helping MHEs in Malaysia. There are two characteristics of roles of Islamic banking institutions in helping MHEs such as the monitoring system and training assistance for MHEs. It also suggested that MHEs need to master the culture of high-quality entrepreneurs such as efficient, systematic, and competitive financial management skills. Finally, both parties; Islamic banking institutions and Muslim entrepreneurs must fulfil their responsibilities accordingly.